Crime hierarchy, victimization and coping results of a qualitative study on the older incarcerated Person's mental health in Switzerland. (March 2023) - Pageau, Félix; Cornaz, Corinne Devaud; Seaward, Helene; Elger, Bernice Simone; Wangmo, Tenzin
Abstract: Background: Incarcerated persons rank themselves according to the crime they have committed. Due to which, those lower in this hierarchy (e.g., paedophiles) are bullied. The goal of this paper was to better knowledge on older incarcerated adults' experiences of crime and social hierarchy in prisons. Methods: Our results comprise data from 50 semi-structured interviews with older incarcerated persons. Data was assessed following thematic analysis. Results: Our research showed that crime hierarchy occurs in prison and is recognized by older incarcerated individuals. Also, a social hierarchy based on various characteristics (e.g., ethnicity, education, language, mental health) is established within detention centres. This hierarchy is put forth by all persons deprived of liberty, but mostly by the ones at the bottom of the crime hierarchy, thus using it to portray themselves as better human beings than other incarcerated adults. They use the social hierarchy to cope with bullying whilst exhibiting coping mechanisms, such as the narcissistic facade. A concept we put forth as a novel idea. Discussion: Our results show that crime hierarchy prevails in prison. Also, we explain the social hierarchy based on ethnicity, education, and other characteristics. Hence, being a victim of bullies, make lower-ranked (on the crime hierarchy) persons resort to social hierarchy to portray themselves as better individuals. This should not be considered as a personality disorder, but rather a narcissistic facade.